Médialité et interprétation contemporaine des premières guerres de Religion - Haug-Moritz, Gabriele (Ateliers des Deutschen Historischen Instituts Paris, 2014)
This work is a compendium of papers presented in a workshop at the German Historical Institute in Paris in 2012 under the direction of Gabriele Haug-Mortiz and Lother Schilling. The essays focus on contemporary interpretations of the first French wars of religion prior to the St. Bartholomew's Day massacre and how these events were portrayed in the media, thereby opening up new research perspectives on a previously neglected field of study.